Analyzing the effects of the Russian-Ukrainian war on Nigeria’s agrifood systems and policy responses - Asante-Addo, Collins; Mockshell, Jonathan; Ritter, Thea; Andam, Kwaw S. (2023)
This policy brief examines the consequences of the Russia-Ukraine war on fertilizer and food commodities in Nigeria and the actions policymakers took in the agriculture sector in response to the war. This brief examines data from publicly available sources and policy responses from government documents and online newspapers. The results show that the Russia-Ukraine war has led to shortages in fertilizer availability, leading to high prices of fertilizer. Likewise, prices of major food commodities, such as maize, rice, wheat and cooking oils, have been on the rise. The impacts of the Russia-Ukraine war have exposed the country’s vulnerable agrifood system and weakened the local currency, leading to foreign exchange shortages and high inflation rates. Nigeria has taken some steps to directly respond to the Russia-Ukraine war, including seeking alternative suppliers of grains, approving imports of genetically modified, drought-resistant wheat, and establishing a private fertilizer plant. Careful consideration should be given to increasing agricultural and food production by promoting technologies to increase the productivity of major food crops.